(untitled) (Cadernos de Sociomuseologia, 2009)
"The tragedy began not when the liberation of the country as a whole ruined, almost automatically, the small hidden islands of freedom that were doomed anyhow, but when it turned out that there was no mind to inherit and to question, to think about and to remember." -Hannah Arendt, Between Past and Future "It is 1971, and Mirek says that the struggle of man against power is the struggle of memory against forgetting." -Milan Kundera, The Book of Laughter and Forgetting "Blade Runner", o filme de Ridlley Scott traduzido por "O Caçador de Andróides" - está de volta, dez anos após seu lançamento, trazendo, novamente, as imagens do desenvolvimento tecnológico e declínio urbano retiradas da obra de Philip K. Dicke e veiculando nossos medos e fantasias de perda de identidade e desumanização. O tema, caracterizado tão bem em clássicos do cinema, como "Metropolis", de Fritz Lang; "Tempos Modernos", de Charles Chaplin; e "Citizen Kane", de Orson Welles, não é, portanto, novo e periodicamente volta ao debate.